Public-Private Partnership in Handling Corona Virus Disease 2019 in DKI Jakarta Province - Dwiky Lucky Adiyasha; Izzatusholekha Izzatusholekha (Department of Public Administration, 2021)
With the growing problem conditions and the increasing number of confirmed cases of Covid-19, it requires the DKI Jakarta Provincial Government to collaborate with stakeholders such as the private sector, national companies, and the public in handling Covid-19 in DKI Jakarta Province. This research focuses on the partnership between the DKI Jakarta Provincial Government and the private Human Initiative and Agile Innovation Labs companies. The purpose of this study is to describe and analyze public private partnerships in handling Covid-19 in DKI Jakarta Province. This study uses a qualitative approach with a descriptive method. In the analysis of this study using the theory proposed by Yusuf et al (2006) with three major variables, namely: (1) Process Factor, (2) Partner Factor, and (3) Structural Factor. The data analyzed are the results of interviews, observations, and document review at the Regional Cooperation Bureau, the Secretariat of DKI Jakarta Province. The results of the study show that from this multi-stakeholder partnership relationship produces various benefits for each party. However, on the partner factor indicator, there are still several obstacles, such as the change of officials in policy-making agencies who do not receive transfer of knowledge from previous officials, so that the partnership process becomes hampered.